Causal effects of gut microbiota on the risk of bipolar disorder: a Mendelian randomization study - Xu, Ran; Liu, Shuo; Li, Lu-yi; Zhang, Ying; Luo, Guang-cheng; Fang, Bo-qin; Wang, Xin-jun (Frontiers in Microbiomes, 2023)
Background: Recent studies have suggested a possible association between gut microbiota and bipolar disorder (BD). However, observational studies are limited and there are variations between the gut microbiota taxa found in different studies.Therefore, we aimed to explore whether there is a causal relationship between gut microbiota and bipolar disorder at the genetic level and to reveal trends in the effect of influential gut microbiota on the development of bipolar disorder.We conducted a Mendelian randomisation (MR) study of summary statistics from a genome-wide association study (GWAS) of gut microbiota and bipolar disorder. Inverse variance weighting (IVW) was used as the primary method of statistical analysis, while results from the MR-Egger method, weighted median, weighted mode, and MR multiplicity residuals and outliers (MR-PRESSO) tests were used for additional validation.Cochrane's Q test, MR-Egger intercept test, and MR-PRESSO global test were used to test MR results for stability and reliability.Result: We identified 13 gut microbial taxa causally associated with bipolar disorder.